Meta-analysis of Outcomes Following Aneurysm Repair in Patients with Synchronous Intra-abdominal Malignancy. Issue 6 (December 2016) - Kumar, R.; Dattani, N.; Asaad, O.; Bown, M.J.; Sayers, R.D.; Saratzis, A.
Abstract : Objectives: The management of concomitant intra-abdominal malignancy (IAM) and abdominal aortic aneurysm (AAA) remains a challenge, even though malignancy is common in an elderly population. By means of systematic review and meta-analysis, the aim was to investigate outcomes in patients undergoing open (OAR) or endovascular AAA repair (EVAR) that have a concomitant malignancy. Methods: A systematic literature review was performed (Medline and EMBASE databases) to identify all series reporting outcomes of AAA repair (OAR or EVAR) in patients with concomitant IAM. Meta-analysis was applied to assess mortality and major morbidity at 30 days and long term. Results: The literature review identified 36 series (543 patients) and the majority (18 series) reported on patients with colorectal malignancy and AAA. Mean weighted mortality for OAR at 30 days was 11% (95% CI: 6.6% to 17.9%); none of the EVAR patients died peri-operatively. The weighted 30-day major complication rate for EVAR was 20.4% (10.0–37.4%) and for OAR it was 15.4% (7.0–30.8%). Most patients had their AAA and malignancy treated non-simultaneously (56.6%, 95% CI, 42.1–70.1%). In the EVAR cohort, three patients (4.6%) died at last follow-up (range 24–64 months). In the OAR cohort 23 (10.6%) had died at last follow up (range from 4 to 73 months). Conclusion: In this meta-analysis, OAR was associated with significant peri-operative mortality in patients with an IAM. EVAR should be the first-line modality of AAA repair. The majority of patients were not treated simultaneously for the two pathologies, but further investigation is necessary to define the optimal timing for each procedure and malignancy.